Robust Optimization Design for Combined Tooth Surface Modification of Helical Gear Pair Considering Load Variation Domain - Xu Wenbo; Yuan Bing; Ma Guoliang; Yu Wentao (Jixie chuandong)
In engineering practice, the load condition of gear pairs is usually not constant, but located in a variable domain. In order to provide an effective method to solve tooth surface modification design of helical gear pairs considering the load variation domain, firstly, the loaded tooth contact equations are constructed using the flexibility matrix method, the efficient model for calculating the flexibility of potential contact points on tooth surface based on the energy and slicing method is established, and the fast calculation model of transmission error of modified helical gear pairs is developed. Secondly, combining tooth profile modification, lead modification and bias modification, based on the robust optimization design theory, a multi-objective mathematical model of combined modification parameters considering the load variation region is proposed aiming to minimize the expectation and variance of the transmission error fluctuations. And then, the non-dominated sorting genetic algorithm with elitist strategy is combined with the calculation model of transmission error, the Pareto frontier solutions of the combined modification parameters are solved, and the robust solution which makes the expectation and variance of transmission error fluctuations smaller is selected. Finally, the transmission error fluctuation of the robust modified helical gear pair considering the load variation domain is investigated. The results show that the modified tooth surface obtained by the proposed method is robust to the load variation.